Locus of control and individual learning: the moderating role of interactional justice. (13th April 2015) - Cappetta, Rossella; Magni, Massimo
<x xml:space="preserve">Abstract</x> Organizations are increasingly investing in training programs for building managerial skills, with a special focus on employees considered 'talents' who must be prepared to cover strategic roles within the organization. One of the main goals of such programs is to develop participants' learning in order to tap their potential in a short time frame, ultimately to gain competitive advantage. However, participant learning is a complex process that can be hindered by different elements related to the characteristics of individuals and the context in which they act. In our research, we conducted a field study to analyze how the individual trait of locus of control (LOC) may negatively affect learning. Moreover, our study indicates that the contextual characteristic of interactional justice mitigates the negative effect of LOC on individual learning. We provide theoretical contributions and suggestions for managers in the light of our results.